PENCEGAHAN FRAUD DENGAN FRAUD CONTROL PLAN: KASUS PADA MANAJEMEN RUMAH SAKIT BLUD DI INDONESIA - Saring Suhendro; Sari Indah Oktanti Sembiring (Faculty of Economics and Business, 2023)
Internal Control is expected to be able to prevent and detect fraud. The Indonesian government uses the Government Internal Control System (SPIP). Management's understanding of SPIP is crucial to ensuring adequate SPIP is implemented in BLUDs. After SPIP is the Fraud Control Plan, both developed by BPKP and are expected to be able to carry out fraud deterrence in BLUD hospitals in Indonesia. According to IcekAjzen's theory of planned conduct, dishonesty has roots in the individual's psyche and goals. This research seeks to verify that hospital BLUD management understands SPIP management, has positive attitudes about behavior, has subjective standards, perceives that they influence their conduct, and intends to utilize FCP to avoid fraud. Indicators of fraud deterrence and FCP as new ideas are presented in this research. The study was conducted on management working in several BLUD hospitals in Indonesia. The results show that management's fraud prevention actions are based on its intention to implement a Fraud Control Plan.